Dry Chain Complements Disaster Preparedness, Food, Feed, Nutrition and Health Security to Alleviate Hunger and Poverty - Dahal, Peetambar. (Tufts University. Tisch Library., 2019)
This poster brings awareness about the primary preventive "Dry Chain" intervention for disaster preparedness and to improve nutrition and food security and alleviate hunger and poverty.; Feed the Future Innovation Lab for Nutrition, USAID Contract No. AID-OAA-L-10-000006, managed by Tufts University's Gerald J. & Dorothy R. Friedman School of Nutrition Science and Policy